"Boom, Headshot!": Effect of Video Game Play and Controller Type on Firing Aim and Accuracy. (October 2014) - Whitaker, Jodi L.; Bushman, Brad J.
Video games are excellent training tools. Some writers have called violent video games "murder simulators." Can violent games "train" a person to shoot a gun? There are theoretical reasons to believe they can. Participants ( N = 151) played a violent shooting game with humanoid targets that rewarded headshots, a nonviolent shooting game with bull's-eye targets, or a nonviolent nonshooting game. Those who played a shooting game used either a pistol-shaped or a standard controller. Next, participants shot a realistic gun at a mannequin. Participants who played a violent shooting game using a pistol-shaped controller had 99% more headshots and 33% more other shots than did other participants. These results remained significant even after controlling for firearm experience, gun attitudes, habitual exposure to violent shooting games, and trait aggressiveness. Habitual exposure to violent shooting games also predicted shooting accuracy. Thus, playing violent shooting video games can improve firing accuracy and can influence players to aim for the head.